Pendampingan Pembuatan Brand Identity Kemasan Produk bagi Usaha Mikro Kecil dan Menengah - Hasbullah; Christofer Satria; I Nyoman Subudiarta; Lanang Sakti (Jurnal Ilmiah Pengabdian dan Inovasi, 2025)
Mentoring for product branding and packaging design for Micro, Small, and Medium Enterprises (MSMEs) is a strategic step to increase product competitiveness and sales value. MSMEs often face challenges in developing a strong brand identity and attractive packaging due to limited knowledge, resources, and access to professional design. However, what steps should be taken by MSME actors to improve their brand visuals so they can compete in the national market? The purpose of this mentoring is to guide and provide knowledge to MSME actors in creating a strong brand and functional, esthetic packaging that aligns with the target market. The mentoring methods include training, consultation, and hands-on practice in logo design, color selection, typography, and packaging materials. The impact of this activity is expected to improve product image, expand market share, and drive business growth. In conclusion, this mentorship not only helps MSMEs with design aspects but also strengthens product positioning amidst increasingly fierce business competition.